Design Kualitas Electronic Word of Mouth terhadap Kinerja Pemasaran Melalui Brand Image - Selvi, Maria Jenia; Hiong, Lauw Sun (Jurnal Informatika Ekonomi Bisnis, 2025)
The ease of access to capital for MSMEs has led to their continued growth. It is known that food and beverage businesses in Pontianak are very diverse, and entrepreneurs can strive to build a positive image, for example by developing the appeal of their products, starting from unique packaging, guaranteed product quality, and marketing methods, both digitally and non-digitally. A good image plays an important role and can encourage existing customers to provide positive reviews. A strategy that entrepreneurs can implement in marketing is to utilize electronic word of mouth, with this information about products conveyed through a good brand image by customers will ultimately increase sales and profits. The study used a quantitative method and a causal approach, namely examining the cause-and-effect relationship between the variables EWOM (x), brand image (z) and marketing performance (y). Data were collected through a questionnaire based on a numeric rating scale, namely a value of 1 to 10. The research population was MSMEs in the food and beverage sector in Pontianak. The sample determined was 147 respondents with a purposive sampling technique, and the data were analyzed using analysis of moment structures (AMOS). The results of the study indicate that electronic word of mouth (EWOM) influences brand image, marketing performance, brand image, and marketing performance through brand image.